Integrating Technology-Enhanced Learning to Foster Student Autonomy and Critical Thinking in Higher Education - Permatasari, Intan; Maulana, Ahmad Rizky (PT. Technology Laboratories Indonesia (TechnoLabs), 2025)
This study explores the effectiveness of online learning in enhancing learning independence and critical thinking skills among higher education students. The shift to digital education, accelerated by global events, has raised important questions about its pedagogical impact on core academic competencies. A quantitative descriptive correlational method was employed, involving 217 undergraduate students from various faculties who had experienced at least two semesters of online learning. Data were collected using a structured questionnaire consisting of three components: perceptions of online learning effectiveness, self-directed learning readiness, and critical thinking disposition. The results showed a positive and significant relationship between the effectiveness of online learning and both learning independence (r = 0.654) and critical thinking (r = 0.611). Furthermore, regression analysis confirmed that online learning effectiveness significantly predicts improvements in both skills. These findings suggest that well-structured online learning environments support students in becoming more autonomous and reflective thinkers. However, disparities in digital literacy and access still present barriers to optimal outcomes. This research highlights the need for higher education institutions to design inclusive, interactive, and learner-centered online platforms that actively support the development of essential 21st-century competencies. Online learning, when thoughtfully implemented, can serve as a powerful medium to nurture student independence and analytical capacity.